O Processo penal e a busca pela verdade - Ferreira, Rosana Miranda (2006)
In this paper we present the performance of the criminal proceeding as an instrument of search for the truth. To base our knowledge on the truth we search the philosophical approach, starting in Greece with Socrates, and finishing on native grounds with Miguel Reale, and in synthesis we describe as each one formulates the knowledge of the truth. For this, we present the truth in the process. We detach real truth as unattainable and impossible to reach, as well as to the president of criminal prosecution, rank that the gauging situation and circumstances, such and which had occurred, never will be obtained to reproduce. We appraise the truths: formal, material, procedural, by approximation and the probability pointing out the most modern trend of the search for certainty close to the judicial truth, this last one happened not of evidence but of a judgment being demarcated by justice primarily. We stress, however, the conquest of the truth, improbable for the criminal proceeding; the persistence in the search of the true reconstitution of the facts is a value that legitimizes the proper criminal persecution. From the presented historical synthesis we search to survey the way of the verification of the truth, ever since the most violent ways of the Inquisition until our days, where a civilian has to wait years for the federal reply. To illustrate the idea we present Franz Kafka, portraying in his workmanship somebody "Before the Law . When disserting the basic right of the access to justice we point out the supremacy of the principle of dignity of the human being, who also must be reflected in the process before the duty of the State "administer justice". We describe some notions of proof, the allegations, the responsibilities, and some of the obstacles inside of the proceeding that interpose as barriers for the search of the truth. We discuss the question of the determined judge to be able or have to evaluate all raised found evidences and even other ones he believes important to include. The decision, finally, emanated from free conviction through arguments and transparency in the briefings, represents the longed for and pursued truth, that exercises, likewise, a social function in the sense of accomplishing the right, applying ethics, to reconcile the society, and to look for the common good